TEACHING PREPOSITION THROUGH ORAL SITUATIONAL LANGUAGE TEACHING METHOD AT THE FIRST YEAR STUDENTS OF SMP NEGERI 33 MAKASSAR - Budiarti Putri Uleng (Jurnal Andi Djemma | Jurnal Pendidikan, 2021)
This research was intended (1) to explain the effectiveness of the use of Oral Situational Language Teaching method in teaching Prepositions, and (2) to find out the most difficult Preposition to be mastered by the first year students at SMP Negeri 33 Makassar. This research used a pre-experimental method. The research applied a purposive sampling technique. The population of this research was the first year students of SMP Negeri 33 Makassar. The seventh grades' total population was 324 students, and a number of samples were 36 students class (IA). The instrument used to collect the data was in multiple choice and essay test which consisted of pre-test and post-test. The variable of this research used two variables, namely: dependent and independent variable. Dependent variable is the students’ understanding about prepositions and independent variable is the Oral-Situational language teaching method. The research findings were that Oral-Situational Teaching Method improved teaching grammar especially for prepositions at the first year students of SMP Negeri 33 Makassar. It was supported by the increase of the students mean score in teh post-test (6.8) as it was classified into good category; it is better than the pre-test in which the students mean score was only (5.6) as it was classified into fairly good category, and the kinds of the prepositions through Oral-Situational teaching method in teaching preposition was more difficult to used preposition of place. The t-test value (6.52) was greater than t-table valuable (2.045). The result of data analysis indicated that there was a significant development of the students’ prepositions by using Oral-Situational Language Teaching Method. Based on the facts, it was concluded that the use of Oral-Situational Language Teaching Method at the first year students of SMP Negeri 33 Makassar was very effective and the students’ difficulties to learn preposition were decreasing or minimalized.